2021
DOI: 10.3389/fendo.2021.669704
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Carboxylated Osteocalcin Correlates With Skeletal Muscle Mass and Risk of Fall in Postmenopausal Osteoporotic Women

Abstract: BackgroundBone and skeletal muscle represent a single functional unit. We cross-sectionally investigated body composition, risk of fall and circulating osteocalcin (OC) isoforms in osteoporotic postmenopausal women to test the hypothesis of an involvement of OC in the bone-muscle crosstalk.Materials and MethodsTwenty-nine non-diabetic, non-obese, postmenopausal osteoporotic women (age 72.4 ± 6.8 years; BMI 23.0 ± 3.3 kg/m2) underwent to: 1) fasting blood sampling for biochemical and hormone assays, including c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Regarding muscles, aging is associated with a decline in skeletal muscle mass and function, causing an alteration of strength, physical performance, and movement. [7][8][9] Estimates for the total decline in the muscle mass between 40 and 80 years of age range from 30% to 50%, and the annual decline in functional capacity is reported to be 1% to 2% after the age of 50 increasing to 3% after 60 years. [10] This process begins sooner in women than in men, when comparing levels of isometric strength of the same muscle group.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding muscles, aging is associated with a decline in skeletal muscle mass and function, causing an alteration of strength, physical performance, and movement. [7][8][9] Estimates for the total decline in the muscle mass between 40 and 80 years of age range from 30% to 50%, and the annual decline in functional capacity is reported to be 1% to 2% after the age of 50 increasing to 3% after 60 years. [10] This process begins sooner in women than in men, when comparing levels of isometric strength of the same muscle group.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, at variance with data reported in mouse models, where GluOC showed endocrine function ( 46 ), our data obtained both in human primary tumor cell and in human cell line cultures, indicated GlaOC as the bioactive molecule able to more consistently elicit modulation of intracellular signaling pathways and of gene expression. Differences observed between mice, where the hormone function is evident for GluOC, and humans, where GlaOC may act as modulator of the parathyroid function in adenomatous glands and of the skeletal muscle ( 47 ), may be related to the different carboxylation status: OC is γ-carboxylated on glutamic acids (Glu) 13, 17 and 20 of protein in mouse, and on Glu 17, 21 and 24 in humans ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitale et al 20 reported that factors associated with risk of falls were not SMI, but rather increased intermuscular adipose tissue. While SMI is a measure of muscle quantity, intramuscular adipose tissue and muscle fibrosis are those of muscle quality and can be evaluated by several devices including computed tomography, magnetic resonance imaging, and ultrasonography 22–24 . The decline in muscle quality is associated with poor muscle strength and physical performance in older adults 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…While SMI is a measure of muscle quantity, intramuscular adipose tissue and muscle fibrosis are those of muscle quality and can be evaluated by several devices including computed tomography, magnetic resonance imaging, and ultrasonography. [22][23][24] The decline in muscle quality is associated with poor muscle strength and physical performance in older adults. 25,26 Yamada et al 23 reported that not only lower muscle quantity but also muscle quality decreases led to higher incidents of falls.…”
Section: Discussionmentioning
confidence: 99%